Dakwah Berbasis Budaya Lokal: Studi tentang Model-model Dakwah di Jawa Barat - Sarbini, Ahmad (Jurnal Ilmu Dakwah, 2011)
Daâwah and local culture are two variables that giving imfortance characteristic for growing and developing daâwah models in West Java. The meeting of them can constructed models that add teoritical discourse of daâwah and models, such as: adaptive model, interactive model and integrative model. In adaptive model, daâwah process ia natural, madâu is given freedom for adaptation with varieties of behavior and values; in interactive model, the societies(madâu) is posited in equal status, attitude and their views honoured, like that also norms and tradition, so daâwah process can create syntheses between mission with culture really; and in integrative model, daâwah is processed in complexity culture where all elemen mutually prices and stimulated to grow and develop in larger spectrum area.